"Friending" Journalists on Social Media: Effects on Perceived Objectivity and Intention to Consume News. (17th November 2020) - Lee, Jayeon
ABSTRACT: Journalists are increasingly revealing their personal and professional identities through social media. Drawing on expectancy violation theory, this experimental study ( N  = 267) examines the influence of a journalist's self-disclosure through social media on audience perceptions of objectivity and intention to consume the journalist's news product. Analyses reveal that journalists' self-disclosure positively affects news-consumption intention while negatively influencing objectivity perceptions. The positive direct effect of self-disclosure on audience behavioral intention is particularly strong when self-disclosure is coupled with a journalist's direct social media engagement with audience members, but this positive effect is counter-balanced by a sizeable negative indirect effect on behavioral intention through perceived objectivity as mediator. The findings of this study present a complex picture that places a news organization's social media practices in direct conflict with its traditional normative ideals, and its ultimate effect on audiences is rather positive than negative. Practical implications of journalists' social media activities are discussed.